Study on Issues and Challenges Faced in Secondary School Education: - (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Education is the backbone of each nation. A nation won't almost certainly survive in the aggressive world, if its education framework isn't capable of contributing for its advancement. Indian education framework is broadly scrutinized in multi-measurements for its inability to make required employability in its understudies as indicated by the business prerequisites and its failure to add to inclusive growth in the country all in all. To accomplish a higher level of association of corporate with the secondary education part, it is imperative that the difficulties of the secondary education segment be distinguished and tended to. Secondary education fills in as a connection between the elementary and advanced education, and plays a significant role in this regard. A tyke's future can depend a ton on the kind of education shehe gets at the secondary dimension. Aside from grounding the foundations of education of a youngster, secondary education can be instrumental in molding and directing the kid to a brilliant future. This phase of education serves to precede onward higher secondary stage just as to give nonexclusive competencies that cut crosswise over different domains of learning just as skills.